(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2014)
In this qualitative research paper, I focus on sociocultural transformations lived and recognized by children and young people belonging to the Centers of Literary Creation organization in the City of Carora, Lara State, Venezuela, which devotes to the education of poetry, understanding the latter as social capital generator. The research was guided by the concepts of social capital, social meaning and human development, articulated for their own outcomes, basing them on the social capital theory, social construction of meanings and the human Development approach. I use the biographical method, life histories modality and opened interviews, as fundamental research techniques for a methodological approximation, such techniques have a combination made of my own. I carry out a temporary combined analysis to the biographical material and a dialogical analysis to opened interviews, from which I make a contrast and integration where I interpret, based on the testimonies of the experiences of a group of children and young people belonging to the CCL, the sociocultural transformations generated both in their personal and family life which took place from the very moment they joined the Centers of Literary Creation. Among the conclusions, I emphasize their visible changes, recognized at a personal, academic and familiar level, and produced in the participant’s life due to the CCL organization type, which is flexible, and its education methodology.